Identification of differentially expressed genes and SNPs linked to harvest body weight of genetically improved rohu carp, Labeo rohita - Nandanpawar, P.; Sahoo, L.; Sahoo, B.; Murmu, K.; Chaudhari, A.; Pavan kumar, A.; Das, P. (Frontiers in Genetics, 2023)
In most of the aquaculture selection programs, harvest body weight has been a preferred performance trait for improvement. Molecular interplay of genes linked to higher body weight is not elucidated in major carp species.The genetically improved rohu carp with 18% average genetic gain per generation with respect to harvest body weight is a promising candidate for studying genes underlying performance traits. In the present study, muscle transcriptome sequencing of two groups of individuals with significant difference in breeding value belonging to 10th generation of rohu carp was performed using Illumina Hiseq 2000 platform. A total of 178 million paired-end raw reads were generated to give rise to 173 million reads after quality control and trimming. Genome guided transcriptome assembly and differential gene expression produced 11,86,119 transcripts, 451 upregulated and 181 downregulated DEGs between high breeding value and low breeding value (HB & LB) groups. Similarly, 39,158 high quality coding SNPs were identified with Ts/Tv ratio 1.23. Out of a total of 17 qPCR validated transcripts, eight were associated with cellular growth and proliferation and harboured 13 SNPs. The gene expression pattern was observed to be positively correlated with the RNAseq data for genes such as Myogenic factor 6, Titin isoform X11, IGF-1 like, Acetyl CoA and Thyroid receptor hormone beta. A total of 26 miRNA target interactions were also identified to be associated with significant DETs (p value < 0.05). Ggenes such as Myog6, IGF-1 like and Acetyl CoA linked to associated with higher harvest body weight may serve as candidate genes in marker assisted breeding, and SNP array construction for genome wide association studies and genomic selection.